Konsumsi Pakan dan Pertambahan Berat Badan Itik Mojosari yang Diberi Tanaman Ciplukan (Physalis angulata L.): Feed Consumption and Weight Increase of Mojosari Ducks Supplemented with Ciplukan Plant (Physalis angulata L.) - Al Munawar,; Fitriani, Fitriani; Semaun, Rahmawati (Anoa: Journal of Animal Husbandry, 2023)
One alternative to increase livestock productivity is by adding ciplukan plants. The ciplukan plant is an herbal plant that contains chemical compounds that are beneficial to the body of livestock. The research objective was to determine the effect of giving ciplukan plant flour on feed consumption and weight gain in Mojosari ducks. This study used a completely randomized design (CRD) with 4 treatment levels (P1, P2, P3) and P0 as a control. Each treatment was replicated 3 times, so there were 12 combination units, each unit consisting of 5 ducks. So the total ducks observed were 60 Mojosari ducks. The research was carried out using a formula that was applied to Mojosari ducks, P0: without treatment/control, P1: 1% addition, P2: 3% addition and P3: 5% addition. Based on the results of the study, the addition of the ciplukan plant given to ducks showed no significant effect on feed consumption (P>0.05) and had a significant effect on body weight gain (P<0.01).